A pilot and feasibility randomised controlled study of Prolonged Exposure Treatment and supportive counselling for post-traumatic stress disorder in adolescents: a third world, task-shifting, community-based sample. Issue 1 (December 2016) - Rossouw, Jaco; Yadin, Elna; Alexander, Debra; Mbanga, Irene; Jacobs, Tracy; Seedat, Soraya
Abstract Background There is a dearth of empirical evidence on the effectiveness of pharmacological and nonpharmacological treatments for adolescents with post-traumatic stress disorder (PTSD) in developing country settings. The primary aim of this study was to demonstrate that Prolonged Exposure Treatment for Adolescents (PE-A) and supportive counselling (SC) are implementable by nurses in a South African context. A secondary aim was to perform a preliminary analysis of the effectiveness of registered nurses delivering either PE-A or SC treatment to adolescents with PTSD. It is hypothesised that PE-A will be superior to SC in terms of improvements in PTSD symptoms and depression. Method A pilot, single-blind, randomised clinical trial of 11 adolescents with PTSD. Nurses previously naïve to Prolonged Exposure (PE) Treatment and SC provided these treatments at the adolescents' high schools. Data collection lasted from March 2013 to October 2014. Participants received twelve 60–90-min sessions of PE (n  = 6) or SC (n  = 5). All outcomes were assessed before treatment, at mid-treatment, immediately after treatment completion and at 12-month follow-up. The primary outcome, PTSD symptom severity, was assessed with the Child PTSD Symptom Scale–Interview (CPSS-I) (range, 0–51; higher scores indicate greater severity). The secondary outcome, depression severity, was assessed with the Beck Depression Inventory (BDI) (range, 0–41; higher scores indicate greater severity). Results Data were analysed as intention to treat. During treatment, participants in both the PE-A and SC treatment arms experienced significant improvement on the CPSS-I as well as on the BDI. There was a significant difference between the PE-A and SC groups in maintaining PTSD and depression at the 12-month post-treatment assessment, with the participants in the PE-A group maintaining their gains both on PTSD and depression measures. Conclusion The treatment was adequately implemented by the nurses and well-tolerated by the participants. Preliminary results suggest that the delivery of either intervention led to a significant improvement in PTSD and depression symptoms immediately post treatment. The important difference was that improvement gains in PTSD and depression in the PE-A group were maintained at 12-month follow-up. The results of this pilot and feasibility study are discussed. Trial registration Pan African Clinical Trials Registry:PACTR201511001345372, registered on 11 November 2015.